R&D subsidies as drivers of corporate performance in Sslovenia: The regional perspective - Dejan Ravšelj; Aleksander Aristovnik (DANUBE: Law, Economics and Social Issues Review, 2017)
Investment in research and development (R&D) plays a vital role in economic growth. Therefore, the crucial role of government is to encourage companies to develop new knowledge, skills, and innovations in order to achieve greater competitiveness, employment creation, and economic development. The aim of this paper is to determine whether R&D subsidies contribute to corporate performance and ascertain whether the relationship between the amount of R&D subsidies and corporate performance is moderated by Slovenian cohesion (NUTS 2 level) and statistical (NUTS 3 level) regions. This paper ultimately tries to classify statistical regions within meaningful groups. Using an OLS regression, a unique dataset of 407 Slovenian companies is analysed for 2014. The empirical results reveal that R&D subsidies have a positive impact on corporate performance and confirm that cohesion and statistical regions can moderate the effect of R&D subsidy on corporate performance. Moreover, the paper provides for the classification of Slovenian statistical regions into four groups.
Keywords: 330; R&D Subsidies; Corporate Performance; Regional Perspective; Slovenia